What is the Role of Trust in Peer Support Schemes for Underrepresented Students? - Claire Hamshire; Mimi Benjamin; Alan Soong Swee Kit (Teaching & Learning Inquiry: The ISSOTL Journal)
The purpose of this study was to explore how peer support schemes can be used to facilitate meaningful relationships and a sense of belonging for underrepresented students. Using three case studies, the study explored and compared peer support leaders’ narratives about their experiences at three universities: one in the United Kingdom (UK), one in the United States (USA), and the other in Singapore. One-to-one interviews and focus groups were completed with 25 students (15 in the UK, four in the USA, and six in Singapore) to explore their perceptions and experiences of being a peer support lead within their institution. These three case studies (one at each institution) explore the multifaceted concept of belonging in order to identify the relative influences of social connection, shared culture/experiences and interpersonal trust. The results demonstrated that the students were aware of the challenges faced by underrepresented students and how peer support schemes can facilitate belonging. Whilst the three settings are diverse, the findings demonstrate that supporting learning transitions and the navigation of liminal spaces through peer support can encourage trust, belonging, and student success. We propose a conceptual model for considering how social connection, shared culture/experiences, and interpersonal trust can contribute to the central goal of belonging. This conceptual model can be used as a resource to support consideration of peer support schemes for underrepresented students that can be developed to support student belonging.